Quantum Materials: Semiconductor‐to‐Metal Transition and Quasiparticle Renormalization in Doped Graphene Nanoribbons (Adv. Electron. Mater. 4/2017). (April 2017) - Senkovskiy, Boris V.; Fedorov, Alexander V.; Haberer, Danny; Farjam, Mani; Simonov, Konstantin A.; Preobrajenski, Alexei B.; Mårtensson, Niels; Atodiresei, Nicolae; Caciuc, Vasile; Blügel, Stefan; Rosch, Achim; Verbitskiy, Nikolay I.; et al.
Abstract : Lithium doping of quasi‐1D graphene nanoribbons aligned on a stepped gold surface changes the electronic properties of the nanoribbons from semiconducting to a metal and causes a renormalization of the effective electron mass and the band gap. In article 1600490, B. Y. Senkovskiy et al. introduce these doped graphene nanoribbons as a new tunable quantum material with high potential for use in basic research and various applications.